Development of strategies to promote healthy sexuality based on Iranian girls perspective about the role of virginity in the construction of their sexuality: an explanatory sequential mixed method study protocol - Somayyeh Naghizadeh; Raziyeh Maasoumi; Farideh Khalajabadi-Farahani; Mojgan Mirghafourvand (BMC, 2022)
Plain language summary Custom, culture and religion in many communities impose virginity on the women of their communities. According to the traditional and conservative Iranian culture, premarital sexual relations are forbidden, female virginity is honor, and it is valuable and necessary for a girl to maintain and take care of her virginity. Attitudes toward sexual relationship and its moral aspects have changed dramatically in many parts of the world in recent decades. Iran, as a conservative society, is no exception to this rule and has experienced substantial social and attitudinal changes over the past decades. This is a two-stage study; an explanatory sequential mixed-methods follow-up design will be employed in the first stage, which consists of two quantitative and qualitative phases. At first quantitative data collection and analysis will be conducted, then the findings inform qualitative data collection and analysis. The findings of two phase will be integrated for further explanation and interpretation to be used in the second stage. In the second stage of the study, the researchers will develop appropriate strategies for the girls' sexual health promotion by a combination of the relevant experts' views obtained in the nominal group meeting and the results extracted from a review of literature as well as the results of the quantitative and qualitative phases of the first stage. it seems that the present study, by employing a better quantitative and qualitative approach, can clarify the young generation's view in the socio-cultural background of Iran and explore the possible inconsistency and contradictions in the modern Iranian society to determine whether the traditional view of the concept of virginity in Iran is still dominant, or it has been changed by factors such as modernization, global communications, influence from advanced Western societies.